Sejarah Perkembangan Latihan Perguruan di Malaysia: Satu Tinjauan - Lee , Chee Ying (Penerbit Universiti Sains Malaysia, 1981)
The Second World War has either created or accelerated political, economic, sosial and educational changes, particularly in the newly independent developing countries of which our country Malaysia is one. These new changes have brought about many challenges which affect educational policy, aims, organisation and curricula. The function of school has been seen as changing and this inevitably has affected the education and tralning of teachers. In Malaysia, education is seen as an instrument of national integration and development; and teacher education is perhaps the most important part of this, because teachers are the agents responsible for translating educational policies into reality